Bimetallic sulfide nanoneedle arrays for lithium ion storage: monocrystalline versus polycrystalline. (August 2022) - Luo, Junfeng; Ou, Xun; Zhu, Licai; Zhang, Jiliang; Chen, Feikuo; Liang, Dongjian; Gao, Aimei; Hu, Jiawei; Chen, Zhishen; Zhao, Ruirui
Abstract: Growing mixed metal sulfides onto conductive substrates is promising in constructing self-supported flexible electrodes. However, most mixed metal sulfides grown on conductive substrates exhibit polycrystalline properties, while single crystallites are rarely reported due to the Kirkendall effect during the anion exchange process. In this work, single-crystalline CoNi2 S4 directly grown on carbon cloth is obtained via tuning the diffusion of involved species with the help of fluorine ions during the anion exchange process. The received single-crystalline CoNi2 S4 exhibits better electrochemical properties than the polycrystalline counterpart, establishing its significance as an electroactive material for lithium-ion batteries. Ex -situ data indicate that the single-crystalline CoNi2 S4 particles exhibit local homogeneity and higher active material utilization upon lithiation/delithiation process, accounting for the enhanced electrochemical performance. These results highlight the importance of single-crystal active materials in constructing self-supported electrodes and reveal a promising opportunity for obtaining high-performance flexible electrodes. Graphical abstract: Image 1 Highlights: Single-crystalline CoNi2 S4 directly grown on carbon cloth is obtained for the first time. Single-crystalline CoNi2 S4 exhibit better electrochemical properties than its counterpart. Ex -situ data indicate better morphological integrity of the single-crystalline CoNi2 S4 upon lithiation/delithiation.